Discovery and characterization of cysteine-rich peptides from Acanthopanax trifoliatus - Goh, Jia Xuan (2017)
Cysteine-rich peptides (CRPs) are a family of mini-proteins found in various organisms that have a molecular mass of 2 to 5 kDa and are reported to contain 6 to 10 cysteine residues. The cysteine residues inter-cross to form disulfide bonds which grant CRPs a robust 3dimensional configuration, providing resistance against thermal, enzymatic and pH degradation. As such, they are speculated to be the reason behind the biological activity of orally-taken herbal decoctions. In this study, a CRP of weight 3670 Da was successfully isolated from crude Acanthopanax trifoliatus extract, which leaves are widely used in traditional Chinese medicine. It was termed as aT3670 and from de novo sequencing, was discovered to have a sequence of QVCSTAGQSCGGEQVCCDGCICNSKFIRPYCFGEC. Query via NCBI tBLASTn search uncovered that aT3670 shares similar homology to numerous peptides. All the peptides were observed to contain a similar cysteine motif of CC-CC-C-C-C. Hence, the disulfide connectivity of aT3670 was speculated to be as follows, Cys I–IV, Cys II–V, Cys III–VI, forming a cystine knot with an additional disulfide bond of Cys VI–VIII. This project provides further insight into the characterization and sequencing of aT3670 for future possible investigations as a potential orally active drug.